PENGARUH VALENSI KATION DALAM RUANG-ANTAR LAPISAN VERMIKULIT TERHADAP PEMBENTUKAN DAN KARAKTERISTIK KIMIA ALUMINIUMHIDROKSIVERMIKULIT - Iskandar Iskandar (Jurnal Ilmu Tanah dan Lingkungan, 2005)
Aluminumhydroxy-smectite (AHS), known also as pillared clay, has some specific characteristics such as wide specific surface area, high basal spacing, and stable at significant high temperature. The AHS was produced from smectite and polymer aluminumhydroxy. In the industrial sector, this product can be used as cracking-catalyst, absorber, and molecular sieve up to 500°C. A similar product can be constructed from vermiculite, and the aluminumhydroxy-vermiculite (AHV) is predicted to have better thermal stability than AHS due to a higher charge density of vermiculite that adsorbs more aluminumhydroxy than that of smectite.Related to the above background the objectives of the research were to study the effects of cation valence in the interlayer space of vermiculite using Li and Ml ions in the formation process and the chemical characteristics of AHV. Li and Mg-vermiculites with different particle sizes are reacted with polymer aluminum-hydroxy' at 100 °C temperature. Solution of 2% Locron was used as a source of aluminum-hydroxy. The products were characterized by chemically and mineralogica/~v. The chemical characteristic includes total chemical analysis, whereas the mineralogical characteristic comprises basal spacing identification that was measured with an X-ray diffractometer (XRD). The results indicated that the AHV produced from Li-vermiculite showed peaks of 1.86 nm and 1.41-1.45 nm with increasing intensity of the 1.86 nm peaks as the particle size was finer. The AHV produced from Mg-vermiculite showed only a peak of 1.45 nm, whereas the 1.84 nm peak can on~v be identified as a shoulder. The AHV with a peak of 1.86 nm (AHV-I.86) can keep its basal spacing to 1.68 nm after 3 hours of heating at a temperature of 700°C, whereas the AHV-I.45 nm shrinkages to 1.10/0.98 nm at the same treatments. Chemical analysis showed that the inter/oyer space of the AHV-I.86 consists of more aluminum-hydroxy than that of the AHV-I.45. Ratio o(OH/AI o(the interlayer aluminum-hydroxy in the AHV-1.86 was 2.57, whereas that of the AHV-1.45 was 2.40. Keywords: Aluminum hydroxy-smectite, aluminumhydroxy-vermiculite, a pillared clay, polymer aluminumhydroxychloride, smectite. vermiculite